Formation and growth of lithium phosphate chemical gardens. Issue 8 (14th February 2022) - Emmanuel, Michael; Lantos, Emese; Horváth, Dezső; Tóth, Ágota
Abstract : Lithium phosphate tubular structures grow in two stages around a liquid jet despite their linearly increasing volume. Abstract : We show that a chemical garden can be developed from an alkaline metal precipitate using a flow-driven setup. By injecting sodium phosphate solution into lithium chloride solution from below, a liquid jet appears, on which a precipitate grows forming a structure resembling a hydrothermal vent. The precipitate column continuously builds upward until a maximum height is reached. The vertical growth then significantly slows down while the tube diameter still increases. The analysis of the growth profiles has revealed a linear dependence of volume growth rate on the injection rate, hence yielding a universal growth profile. The expansion in diameter, localized at the tip of the structure, scales with a power law suggesting that the phenomenon is controlled by both diffusion and convection.